Effect of Earthworm on Wound Healing: A Systematic Review and Meta-Analysis - Wang, Dong; Ruan, Zhen; Zhang, Rongchao; Wang, Xuejing; Wang, Ruihui; Tang, Zhishu (Frontiers in Pharmacology, 2021)
Background: Earthworm, also called Dilong, has been used as a traditional Chinese medicine for over thousands of years. Recently, some scientists believed earthworm extracts (EE) can promote wound healing. However, its effectiveness remains controversial. We conducted a meta-analysis to evaluate the effect of EE on wound healing based on healing rate. Methods: We comprehensively reviewed literatures in the PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), VIP Database for Chinese Technical Periodicals and WanFang database that have been published until January 2021. Finally, we identified 14 articles (including 16 studies) after the inclusion criteria. Results: EE treatment was associated with improvements in wound healing performance based on wound healing rate (mouse model: weighted mean difference (WMD)=3.55, 95% Confidence Interval (CI): 2.34–4.77, P＜0.00001; rat model: WMD=17.29, 95% CI: 5.75–28.82，P=0.003; rabbit model: WMD=19.29, 95% CI: 9.95–28.64, P＜0.0001). Clinic trials also confirmed that EE could reduce healing time in hospital (WMD=−8.94, 95% CI: −17.75–−0.14, P=0.05). Conclusion: The results of this meta-analysis demonstrated the efficacy of EE on wound healing process. As a corollary, EE can be a useful natural product for wound healing drug development.